Anisotropic nanocrystalline rare earth permanent magnets and preparation methods

By introducing M-Cu or M-Cu-O phases into rare earth permanent magnet ferrite, the problem of coercivity improvement of rare earth permanent magnet ferrite in the prior art has been solved, and efficient and economical magnetic performance improvement has been achieved.

JP7658651B1Active Publication Date: 2025-04-08SICHUAN UNIV
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
JP2024532200
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-16
Filing Date
2023-12-21
Publication Date
2025-04-08
Estimated Expiration
2043-12-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the coercivity of rare earth permanent magnet ferrite while maintaining cost-effectiveness.

Method used

By introducing M-Cu or M-Cu-O phase into the rare earth permanent magnet ferrite, M is calcium or magnesium, where the Cu content is between 10-60 wt%, the formed rare earth permanent magnet ferrite has a higher coercivity.

Benefits of technology

It is achieved that the coercivity of rare earth permanent magnet ferrite is significantly improved without increasing the use of rare earth elements, thereby improving magnetic performance and reducing material preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658651000001_ABST
    Figure 0007658651000001_ABST
Patent Text Reader

Abstract

The present invention discloses anisotropic nanocrystalline rare earth permanent magnets and a preparation method thereof, the permanent magnets comprising a RE-Fe-B matrix phase and a second phase, the RE-Fe-B matrix phase being a regularly ordered main phase, RE2Fe 14 The REFe2Fe3O4 sheet-like nanocrystals and the RE-rich phase located around the grains of the main phase are the main phase. 14 The average crystal grain size in the length direction of the sheet-like nanocrystals of B is 70-800 nm, and the average crystal grain size in the thickness direction is 30-200 nm, and the second phase includes at least one of M-Cu phase and M-Cu-O phase, where M is at least one of Ca and Mg. The present invention utilizes Ca and / or Mg in the M-Cu alloy to reduce rare earth oxides at the interface of the RE-Fe-B magnetic powder, improve the distribution of the rare earth rich phase, and refine the crystal grains of the nanocrystals, which are the main phase. In addition, the second phase distributed at the interface of the magnetic powder suppresses the formation of coarse grains at the interface of the magnetic powder, optimizes the microstructure of the magnet, and improves the coercive force.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to a Chinese patent application filed with the China Patent Office on February 16, 2023, with application number CN202310120822.2 and title "Anisotropic nanocrystalline rare earth permanent magnet and preparation method", the entire contents of which are incorporated herein by reference. The present invention relates to the technical field of rare earth permanent magnet materials, in particular to anisotropic nanocrystalline rare earth permanent magnets and preparation methods. [Background technology]

[0002] RE-Fe-B rare earth permanent magnetic alloys have excellent hard magnetic properties, and are currently the permanent magnetic material with the highest application performance, and have become an indispensable basic material for the development of modern industrial society. In recent years, with the continuous development of industrial technology and the continuous expansion of the application range of RE-Fe-B permanent magnetic materials, higher requirements have been put forward for the magnetic performance of RE-Fe-B permanent magnetic materials, so the development of high-performance RE-FE-B permanent magnetic materials has become a hotspot of high-tech research and development in countries around the world.

[0003] Compared with the micron-crystalline RE-Fe-B rare earth permanent magnet, the nanocrystalline RE-Fe-B rare earth permanent magnet has higher corrosion resistance and heat resistance due to its rich grain boundary structure, and can achieve higher coercive force under the same rare earth content, which has already become the rare earth permanent magnet material with the most development potential. In the ideal case, the magnetic performance of anisotropic nanocrystalline RE-Fe-B rare earth permanent magnet is twice that of isotropic nanocrystalline RE-Fe-B rare earth permanent magnet. However, the coercive force of anisotropic nanocrystalline RE-Fe-B rare earth permanent magnet prepared by the actual production process is still far lower than the theoretical value, so at present, researchers have tried various experimental methods to improve the coercive force of rare earth permanent magnets.

[0004] Fuerst and Brewer et al. (Fuerst CD, Brewer EG, Enhanced coercivities in die-upset Nd-Fe-B magnets with diffusion-alloyed additives (Zn, Cu, and Ni), Applied physics letters, 1990, 56(22):2252-2254.) reported that the isolation effect of non-magnetic Cu element at grain boundary can partially improve the coercivity of magnets. After that, a large amount of scientific research work improved the grain boundary phase by adding low melting point RE-Cu phase to grain boundary to improve the coercivity of magnets, but the use of a large amount of RE element inevitably leads to an increase in material preparation cost. Chinese invention patent with application number 201510834685.4 discloses a preparation method of high coercivity nanocrystalline hot deformed rare earth permanent magnet material, which adds high melting point WC phase to improve the coercivity of magnets, but WC is mixed with Nd-rich phase and RE2Fe 14 B main phase, which limits the further improvement of its magnetic performance. Zhang et al. (Zhang T, Liu S, Wu Z, et al., Coercivity and remanence enhancement in hot-deformed Nd-Fe-B magnetsby high-temperature short-term annealing process, 《Journal of Alloys and Compounds》, 2022, 903:163975.) optimized the distribution of Nd-rich phase by suitable heat treatment technology, and diffused some of the rich Nd phase located at the interface of the magnetic powder, which penetrated into the interior of the magnetic powder and improved the coercivity of the magnet. However, there is still a large amount of rare earth oxide at the interface of the magnetic powder, and the high melting point rare earth oxide has difficulty penetrating into the interior of the magnetic powder, limiting the further improvement of the coercivity of the magnet.

[0005] Therefore, how to economically and efficiently increase the coercivity of anisotropic nanocrystalline rare earth permanent magnets has become a problem that requires an immediate solution. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] (Fuerst CD, Brewer EG, Enhanced coercivities in die-upset Nd-Fe-B magnets with diffusion-alloyed additives(Zn, Cu, and Ni), 《Applied physics letters》, 1990, 56(22):2252-2254.) [Non-Patent Document 2] (Zhang T, Liu S, Wu Z, et al, Coercivity and remanence enhancement in hot-deformed Nd-Fe-B magnetsby high-temperature short-term annealing process,《Journal of Alloys and Compounds》, 2022, 903:163975.) Summary of the Invention [Problem to be solved by the invention]

[0007] SUMMARY OF THE PRESENT EMBODIMENT The present invention aims to provide an anisotropic nanocrystalline rare earth permanent magnet and a preparation method thereof, which can economically and efficiently improve the coercivity of the anisotropic nanocrystalline rare earth permanent magnet. [Means for solving the problem]

[0008] In a first aspect, the present invention provides an anisotropic nanocrystalline rare earth permanent magnet, which adopts the following technical solutions:

[0009] An anisotropic nanocrystalline rare earth permanent magnet, the rare earth permanent magnet comprising a RE-Fe-B matrix phase and a second phase; The RE-Fe-B matrix phase is a regularly arranged main phase of RE2Fe 14The REFe2Fe3O4 sheet-like nanocrystals and the RE-rich phase located around the grains of the main phase are included. 14 The average crystal grain size in the length direction of the sheet-like nanocrystals of B is 70 to 800 nm, and the average crystal grain size in the thickness direction is 30 to 200 nm. 14 The length-to-thickness ratio of the sheet-like nanocrystals of B is greater than 1.2; The volume fraction of the coarse grain region in the RE-Fe-B matrix phase is 10% or less, and the volume fraction is calculated as the volume of the coarse grain region and the volume of the rare earth permanent magnet, and the coarse grain region refers to an equiaxed crystal region having a crystal grain size of more than 500 nm; The second phase includes at least one of an M-Cu phase and an M-Cu-O phase, where M is at least one of Ca and Mg.

[0010] Optionally, the rare earth permanent magnet is prepared from a raw material powder obtained by mixing RE-Fe-B magnetic powder and M-Cu alloy powder, where M is at least one of Ca and Mg, and the components of the RE-Fe-B magnetic powder are RE, x Fe 100-x-y-z TM y B z and The RE is one or more of La, Ce, Pr, Nd, Y, Dy, Tb, and Ho; the TM being one or more of Co, Zr, Cr, V, Nb, Si, Ti, Mo, Mn, W, Ga, Cu, Al, and Zn; The x, y, and z represent mass fractions of elements, where 26.0≦x≦36.0, 0.14≦y≦8.0, and 0.8≦z≦1.36.

[0011] Optionally, the amount of the M-Cu alloy powder added is 0.1-5.0 wt. % calculated as the mass of the RE-Fe-B magnetic powder.

[0012] Optionally, the M-Cu alloy powder is a Ca-Cu alloy powder, and the mass percentage of Cu in the Ca-Cu alloy powder is 10-60 wt.%, or the M-Cu alloy powder is a Mg-Cu alloy powder, and the mass percentage of Cu in the Mg-Cu alloy powder is 1-50 wt.%, or the M-Cu alloy powder is a Ca-Mg-Cu alloy powder, and the mass percentage of Cu in the Ca-Mg-Cu alloy powder is 10-50 wt.%.

[0013] Optionally, a volume fraction of coarse grain regions in the RE-Fe-B matrix phase is less than or equal to 1%.

[0014] In a second aspect, the present invention provides a method for producing a raw material powder, which is at least one of anisotropic raw material powder and isotropic raw material powder, by mixing an RE-Fe-B magnetic powder including at least one of anisotropic magnetic powder and isotropic magnetic powder with an M-Cu alloy powder, where M is at least one of Ca and Mg; The main phase is RE2Fe 14 and a preparation step of obtaining the anisotropic nanocrystalline rare earth permanent magnet by subjecting the raw material powder to hot working treatment so as to regularly arrange the sheet-like nanocrystals of B.

[0015] Optionally, the RE-Fe-B magnetic powder comprises a nanocrystalline magnetic powder or an amorphous magnetic powder; The nanocrystalline magnetic powder has an equiaxed crystal structure or a sheet-like crystal structure, and the average crystal grain size of the equiaxed crystal structure is 10 to 400 nm, the average crystal grain size in the length direction of the crystal grains of the sheet-like crystal structure is 20 to 500 nm, and the average crystal grain size in the thickness direction of the crystal grains is 10 to 200 nm.

[0016] Optionally, the form of the RE-Fe-B magnetic powder includes sheet-like magnetic powder, granular magnetic powder or irregular magnetic powder, and the length-to-thickness ratio of the sheet-like magnetic powder is 1.2-30.

[0017] Optionally, the hot working process includes at least one of a hot deformation process, a hot extrusion deformation process, a magnetic field oriented sinter forming process, and a mechanically oriented sinter forming process.

[0018] Optionally, the hot deformation process comprises: preparing the raw material powder into a body having a density of 50% to 99.99% at a temperature of room temperature to 800°C; The main phase is RE2Fe 14 and a step of subjecting the base material to hot deformation treatment at a temperature of 600 to 850° C., a deformation amount of 30% to 90%, and a deformation speed of 0.01 to 3.5 mm / s so as to arrange the sheet-shaped nanocrystals of B in a regular pattern.

[0019] Optionally, the hot extrusion deformation process comprises: preparing the raw material powder into a body having a density of 50% to 99.99% at a temperature of room temperature to 800°C; The main phase is RE2Fe 14 and a step of subjecting the base material to hot deformation treatment at a temperature of 600 to 850° C. so as to arrange the sheet-shaped nanocrystals of B in a regular pattern. Optionally, the hot extrusion deformation process comprises: The main phase is RE2Fe 14 and subjecting the raw material powder to hot extrusion deformation at a temperature of 600 to 850°C so as to arrange the sheet-shaped nanocrystals of B regularly, the hot extrusion deformation temperature being 600 to 850°C.

[0020] Optionally, the magnetic field oriented sintering molding process comprises: The anisotropic raw material powder is subjected to an orientation molding process under an external magnetic field condition of 1 to 3 T to prepare a green compact; and performing hot-roll sintering or pressureless sintering on the green compact.

[0021] Optionally, the hot rolling sintering temperature is 450-850° C., the pressure is 50-500 MPa, and the time is 1-60 min.

[0022] Optionally, the pressureless sintering is performed at a sintering temperature of 600 to 850° C. for a time of 10 to 120 minutes.

[0023] Optionally, the mechanically oriented sintering molding process comprises: The method includes a step of subjecting the anisotropic raw material powder (the RE-Fe-B magnetic powder of the anisotropic raw material powder is a sheet-shaped magnetic powder having a length-to-thickness ratio of 1.2 to 30, and the direction of easy magnetization of the sheet-shaped magnetic powder is parallel to the thickness direction of the sheet-shaped magnetic powder) to hot-rolling orientation sintering under a uniaxial pressure of 50 to 500 MPa at a sintering temperature of 450 to 850°C for a sintering time of 1 to 60 minutes.

[0024] Optionally, the anisotropic raw material powder (the RE-Fe-B magnetic powder of the anisotropic raw material powder is a sheet-shaped magnetic powder having a length-to-thickness ratio of 1.2 to 30, and the easy magnetization direction of the sheet-shaped magnetic powder is parallel to the thickness direction of the sheet-shaped magnetic powder) is subjected to room temperature cold rolling molding under uniaxial pressure to obtain a green compact having a density of 40% to 70%; The method includes a step of subjecting the green compact to pressureless sintering at a sintering temperature of 600 to 850° C. for a sintering time of 10 to 120 minutes. Effect of the Invention

[0025] In summary, the present invention has at least one of the following beneficial effects: 1. The present invention provides an anisotropic nanocrystalline rare earth permanent magnet, the rare earth permanent magnet comprising an RE-Fe-B matrix phase and a second phase, the RE-Fe-B matrix phase being an regularly arranged main phase, RE2Fe 14The second phase includes a RE-rich phase located around the sheet-like nanocrystals of B and the crystal grains of the main phase, and the second phase includes at least one of M-Cu phase or M-Cu-O phase, where M is at least one of Ca and Mg. The use of Ca and / or Mg in the M-Cu alloy to reduce the rare earth oxides at the interface of the RE-Fe-B magnetic powder is favorable for removing the rare earth oxides at the interface and improving the distribution of the rare earth rich phase, and can suppress the enrichment of the rare earth rich phase at the interface of the magnetic powder, and can improve the content of the rare earth rich phase between the crystal grains of the main phase inside the magnetic powder. In addition, the second phase distributed at the interface of the magnetic powder can suppress the formation of coarse grains at the interface of the magnetic powder, and can reduce the rare earth oxides at the interface of the main phase of the RE-Fe-B magnetic powder. 14 It is advantageous to refine the crystal grains of the sheet-shaped nanocrystals of B, thereby optimizing the microstructure of the anisotropic nanocrystalline rare earth permanent magnet and improving the coercive force of the magnet. 2. The method for preparing anisotropic nanocrystalline rare earth permanent magnets provided by the present invention has a simple process, the added M-Cu alloy raw materials are easy to obtain, the cost is low, and the main phase RE2Fe 14 It does not react with B, and the preparation process is highly controllable, while at the same time avoiding the increase in cost due to the addition of rare earth. The resulting anisotropic nanocrystalline permanent magnets have excellent performance, are economical and efficient, and are suitable for industrial mass production. [Brief description of the drawings]

[0026] [Figure 1] 1 is an XRD spectrogram of the Ca-Cu alloy powder prepared from the Ca70Cu30 alloy of Example 1. [Diagram 2] FIG. 2 is an SEM image of a cross section of an anisotropic nanocrystalline rare earth permanent magnet prepared in Comparative Example 1. [Diagram 3] 1A-1C are SEM images of the cross sections of anisotropic nanocrystalline rare earth permanent magnets with 0.5 wt.%, 1.0 wt.%, and 2.0 wt.% Ca-Cu alloy powder additives prepared in Example 1. [Figure 4]1A-1C are SEM images of the cross sections of anisotropic nanocrystalline rare earth permanent magnets with 0.5 wt.%, 1.0 wt.%, and 2.0 wt.% Ca-Cu alloy powder additives prepared in Example 1. [Diagram 5] 1A-1C are SEM images of the cross sections of anisotropic nanocrystalline rare earth permanent magnets with 0.5 wt.%, 1.0 wt.%, and 2.0 wt.% Ca-Cu alloy powder additives prepared in Example 1. [Figure 6] Figure 6(a) is an SEM-EDS spectrogram of the interface of magnetic powder inside the anisotropic nanocrystalline rare earth permanent magnet prepared in Comparative Example 1, and Figure 6(b) is an SEM-EDS spectrogram of the interface of magnetic powder inside the anisotropic nanocrystalline rare earth permanent magnet prepared in Example 1 with the addition of 1.0 wt.% Ca-Cu alloy powder. [Figure 7] 6 is a TEM-EDS spectrogram of the Ca-Cu-O phase region at the interface of magnetic powders within the anisotropic nanocrystalline rare earth permanent magnet prepared with the addition of 1.0 wt. % Ca-Cu alloy powder in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] The present invention provides anisotropic nanocrystalline rare earth permanent magnets and preparation methods, and in order to make the objectives, technical solutions and effects of the present invention clearer, the present invention will be described in more detail below. It should be understood that the specific examples described herein are only used to illustrate the present invention, and are not used to limit the present invention.

[0028] At present, anisotropic nanocrystalline RE-Fe-B rare earth permanent magnets mainly include two preparation methods: the first method is to densify nanocrystalline or amorphous magnetic powder to form a green body, and then to carry out thermoplastic processing on the green body to form the main phase RE2Fe in the green body through the thermodynamic coupling effect; 14 The sheet-like nanocrystals of B are regularly arranged, i.e., the main phase RE2Fe 14The first type is to prepare an anisotropic nanocrystalline rare earth permanent magnet by aligning the c-axes of the sheet-shaped nanocrystals of B in parallel; the second type is to prepare an anisotropic nanocrystalline rare earth permanent magnet by subjecting anisotropic magnetic powder having a nanocrystalline structure to magnetic field orientation and sintering densification treatment.

[0029] After long-term research, the applicant has found that, through controlling the preparation process, anisotropic nanocrystalline RE-Fe-B rare earth permanent magnets can achieve single domain size nanocrystalline grains, but the coercivity is much lower than the empirical expectation, which is mainly related to the magnet microstructure. The anisotropic nanocrystalline rare earth permanent magnets have a main phase of RE2Fe 14 The RE-rich phase is distributed around the grains of the main phase, the former provides the magnet with high saturation magnetization strength, and the latter has a magnetic coupling removal effect that ensures that the magnet has high coercivity. The grain size of the main phase and the components and distribution of the RE-rich phase are the determining factors of the coercivity of the rare earth permanent magnet. After extensive research, the applicant has found that there are mainly three reasons that lead to the reduction of the coercivity of the anisotropic nanocrystalline RE-Fe-B rare earth permanent magnet. On the one hand, in the preparation process, there exists stress concentration and local overheating phenomenon at the interface of the magnetic powder, and the grains at the interface region are prone to grow abnormally, forming coarse grains, resulting in a reduction in coercivity; on the other hand, the grain boundary phase between the grains of the nano main phase has a high iron magnetic element content, and exchange coupling occurs between the grains of the main phase, resulting in a reduction in coercivity; finally, the activity of the rare earth rich phase is high, which can be oxidized quickly at room temperature, forming rare earth oxides, reducing the magnetic coupling removal effect of the rare earth rich phase, resulting in a reduction in coercivity.

[0030] In the course of research, the applicant was surprised to discover that low-melting-point M-Cu alloys, i.e., Ca-Cu alloys (up to 490°C), Mg-Cu alloys (up to 485°C) or Ca-Mg-Cu alloys, could be produced by alloying Ca and / or Mg with Cu. The added M-Cu alloys were found to have a low melting point and a low melting point of about 1000°C. 14The M-Cu alloy, which does not react with B and has a low melting point, can flow, diffuse and distribute uniformly during magnet preparation, without the need to crush extremely small powders, and can avoid serious oxidation of Ca or Mg. Compared with single Ca powder and Mg powder, the M-Cu alloy has better oxidation resistance, thereby maintaining the reduction activity of Ca and Mg. During hot processing, the M-Cu alloy can reduce the rare earth oxides on the surface of the RE-Fe-B magnetic powder, thereby increasing the fluidity of the rare earth rich phase and suppressing the enrichment of the rare earth rich phase at the interface, which can diffuse better on the surface of the main phase crystal grains inside the magnet, increasing the pinning effect of the grain boundary phase on the domain wall, and improving the coercivity of the magnet. In addition, the M-Cu phase or the M-Cu-O phase generated in situ exists at the interface of the RE-Fe-B magnetic powder inside the magnet, which can suppress the formation of coarse grains during hot processing and is favorable for refinement of the main phase crystal grains, and further improving the coercivity of the anisotropic nanocrystalline rare earth permanent magnet.

[0031] The present invention was achieved based on the above studies.

[0032] The present invention provides an anisotropic nanocrystalline rare earth permanent magnet, the rare earth permanent magnet comprising an RE-Fe-B matrix phase and a second phase, the RE-Fe-B matrix phase being an regularly ordered main phase, RE2Fe 14 The REFe2Fe3O4 sheet-like nanocrystals and the RE-rich phase located around the grains of the main phase are the main phase. 14 The c-axes of the sheet-like nanocrystals of B are aligned parallel to each other, forming the main phase of REFe 14The average crystal grain size in the length direction of the sheet-like nanocrystals of B is 70 to 800 nm, preferably 100 to 600 nm, more preferably 150 to 400 nm, even more preferably 200 to 400 nm, even more preferably 210 to 350 nm, even more preferably 230 to 300 nm, the average crystal grain size in the thickness direction is 30 to 200 nm, preferably 50 to 150 nm, more preferably 70 to 120 nm, and the length to thickness ratio of the sheet-like nanocrystals is greater than 1.2, preferably 1.5 or more, more preferably 2 or more. The second phase includes at least one of an M-Cu phase or an M-Cu-O phase, and M is at least one of Ca and Mg.

[0033] The rare earth permanent magnet according to the present invention is prepared from a raw material powder obtained by mixing RE-Fe-B magnetic powder and M-Cu alloy powder, wherein M is at least one of Ca and Mg, and the components of the RE-Fe-B magnetic powder are RE, x Fe 100-x-y-z TM y B z wherein RE is one or more of La, Ce, Pr, Nd, Y, Dy, Tb, and Ho, and preferably at least one of La, Ce, Pr, Nd, and Y; TM is one or more of Co, Zr, Cr, V, Nb, Si, Ti, Mo, Mn, W, Ga, Cu, Al, and Zn, and preferably at least one of Co, Zr, Cr, V, Nb, Ga, and Mo; and wherein x, y, and z denote mass fractions of elements, where 26.0≦x≦36.0, 0.14≦y≦8.0, and 0.8≦z≦1.36.

[0034] When calculated as the mass of the RE-Fe-B magnetic powder, the amount of the M-Cu alloy powder added is 0.1 to 5.0 wt.%, preferably 0.5 to 3 wt.%, more preferably 0.5 to 2.0 wt.%, even more preferably 0.5 to 1.5 wt.%, and even more preferably 0.5 to 1.0 wt.%. The M-Cu alloy powder is distributed at the interface of the magnetic powder inside the RE-Fe-B magnet, and if the amount added is too low, it will not be useful in improving the distribution of the grain boundary phase or suppressing the coarsening of crystal grains, and if the amount added is too high, the M-Cu alloy powder will aggregate and will not be useful in improving the performance of the nanocrystalline rare earth permanent magnet. The mass percentage of Cu in the Ca-Cu alloy powder is 10-60wt.%, preferably 15-55wt.%, more preferably 20-50wt.%, the mass percentage of Cu in the Mg-Cu alloy powder is 1-50wt.%, preferably 5-45wt.%, more preferably 10-45wt.%, and the mass percentage of Cu in the Ca-Mg-Cu alloy powder is 10-50wt.%. The average particle size of the M-Cu alloy powder is 300μm or less, preferably 200μm or less, more preferably 100μm or less. A part of the M-Cu alloy powder reduces the rare earth oxide to generate the M-Cu-O phase, and the unreacted part is retained as the M-Cu phase, all of which are distributed at the interface of the magnetic powder, and can suppress the crystal grains at the RE-Fe-B interface from growing to form coarse grains. The volume fraction of the coarse grain region in the RE-Fe-B matrix phase is 10% or less, calculated based on the volume of the coarse grain region and the volume of the rare earth permanent magnet, and is more preferably 8% or less, even more preferably 6% or less, even more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, even more preferably 1% or less, 0 or more, or 0.5% or more.The coarse grain region refers to the equiaxed grain region with a crystal grain size larger than 500 nm. The volume fraction of the coarse grain region is calculated as the volume of the coarse grain region and the volume of the rare earth permanent magnet. The volume fraction of the coarse grain region is determined by first testing a cross section parallel to the c-axis (easy axis of magnetization) direction of the magnet using a scanning electron microscope (SEM), and then calculating the average value of the ratio between the sum of the areas of the coarse grain regions and the total area of ​​the magnet in five low-magnification SEM images. The low-magnification SEM images may be at a magnification of 500 or other magnifications, and the measurement of the area of ​​the coarse grain region can be achieved based on this.

[0035] The present invention provides a method for preparing anisotropic nanocrystalline rare earth permanent magnets, A preparation step S1 of mixing an RE-Fe-B magnetic powder and an M-Cu alloy powder to obtain a raw material powder, where M is at least one of Ca and Mg, the RE-Fe-B magnetic powder contains at least one of anisotropic magnetic powder and isotropic magnetic powder, and the raw material powder obtained by mixing contains at least one of anisotropic raw material powder and isotropic raw material powder; The main phase is RE2Fe 14 and a preparation step S2 in which the raw material powder obtained in S1 is subjected to hot working to prepare an anisotropic nanocrystalline rare earth permanent magnet.

[0036] The RE-Fe-B magnetic powder adopts a nanocrystalline magnetic powder or an amorphous magnetic powder, and the nanocrystalline magnetic powder has an equiaxed crystal structure or a sheet-like crystal structure, and the average crystal grain size of the equiaxed crystal structure is 10 to 400 nm, preferably 30 to 200 nm, and more preferably 35 to 150 nm, the average crystal grain size in the length direction of the crystal grains of the sheet-like crystal structure is 20 to 500 nm, preferably 50 to 400 nm, and more preferably 100 to 300 nm, and the average crystal grain size in the thickness direction of the crystal grains is 10 to 200 nm, preferably 30 to 150 nm, and more preferably 50 to 100 nm. The form of the RE-Fe-B magnetic powder can be a sheet-like magnetic powder, a granular magnetic powder or an irregular magnetic powder, in which the length-to-thickness ratio of the sheet-like magnetic powder is 1.2-30, preferably 1.5-30, more preferably 2-20, even more preferably 3-15, and even more preferably 5-10, and the easy magnetization direction of the anisotropic sheet-like magnetic powder is parallel to the thickness direction of the magnetic powder.

[0037] The hot working process in step S2 includes at least one of hot deformation process, hot extrusion deformation process, magnetic field oriented sintering forming process, and mechanically oriented sintering forming process.

[0038] Specifically, the hot deformation process is Step S2.1, in which the raw material powder is prepared into a green body at a temperature of room temperature to 800°C, and the green body has a density of 50% to 99.99%, preferably 70% to 99.99%, more preferably 80% to 99.99%, and even more preferably 90% to 99.99%; The main phase is RE2Fe 14 and step S2.2, in which the base material is subjected to a hot deformation treatment so as to arrange the sheet-like nanocrystals of B in a regular pattern, the hot deformation temperature being 600 to 850°C, preferably 650 to 800°C, the deformation amount being 30% to 90%, preferably 50 to 80%, more preferably 55 to 75%, and the deformation speed being 0.01 to 3.5 mm / s, preferably 0.1 to 2 mm / s.

[0039] Hot extrusion deformation processing is Step S2.1, in which raw material powder is prepared into a green body at a temperature of room temperature to 800°C, preferably nanocrystalline mixed magnetic powder is prepared into a green body at a temperature of room temperature to 700°C, or amorphous mixed magnetic powder is prepared into a green body at a temperature of 600 to 750°C, and the density of the green body is 50% to 99.99%, preferably 70% to 99.99%, more preferably 80 to 99.99%, and even more preferably 90 to 99.99%; The main phase is RE2Fe 14 and step S2.2, in which the base material is subjected to hot extrusion deformation so as to arrange the sheet-like nanocrystals of B in a regular arrangement, the hot extrusion deformation temperature being 600 to 850°C, preferably 650 to 800°C.

[0040] Or the main phase RE2Fe 14 and Step S2' in which the raw material powder is subjected to hot extrusion deformation so as to arrange the sheet-shaped nanocrystals of B in a regular order, the hot extrusion deformation temperature being 600 to 850°C, preferably 650 to 800°C.

[0041] The magnetic field orientation sintering molding process is Step S2.1 of performing orientation molding on the anisotropic raw material powder under an external magnetic field condition of 1 to 3 T, preferably 1.5 to 3 T, to prepare a green compact; Step S2.2, which performs hot rolling and sintering on the green compact, in which the hot rolling and sintering temperature is 450 to 850°C, preferably 650 to 800°C, the hot rolling and sintering pressure is 50 to 500 MPa, preferably 50 to 300 MPa, and the hot rolling and sintering time is 1 to 60 minutes, preferably 5 to 30 minutes; Alternatively, the method includes step S2.2 of performing pressureless sintering on the green compact, in which the sintering temperature for pressureless sintering is 600 to 850° C., preferably 650 to 800° C., and the sintering time is 10 to 120 min, preferably 10 to 60 min.

[0042] The mechanically oriented sintering molding process is Step S2' in which the anisotropic raw material powder is subjected to hot-rolling orientation sintering under uniaxial pressure, the RE-Fe-B magnetic powder of the anisotropic raw material powder is a sheet-shaped magnetic powder, the length-to-thickness ratio of the sheet-shaped magnetic powder is 1.2 to 30, preferably 1.5 to 30, the easy magnetization direction of the sheet-shaped magnetic powder is parallel to the thickness direction of the magnetic powder, the sintering temperature is 450 to 850°C, preferably 650 to 800°C, the uniaxial pressure is 50 to 500 MPa, preferably 50 to 230 MPa, and the sintering time is 1 to 60 min, preferably 5 to 30 min; Alternatively, step S2.1″ is performed on the anisotropic raw material powder by cold rolling at room temperature under uniaxial pressure, and the RE-Fe-B magnetic powder of the anisotropic raw material powder is a sheet-shaped magnetic powder, the length-to-thickness ratio of the sheet-shaped magnetic powder is 1.2 to 30, preferably 1.5 to 30, the easy magnetization direction of the sheet-shaped magnetic powder is parallel to the thickness direction of the magnetic powder, and the density of the green compact is 40% to 70%, preferably 50% to 70%; and Step S2.2″, in which the green compact is subjected to pressureless sintering, the sintering temperature of the pressureless sintering being 600 to 850° C., preferably 650 to 800° C., and the sintering time being 10 to 120 min, preferably 10 to 60 min.

[0043] The present invention will now be further described with reference to specific examples.

[0044] Example 1 This embodiment provides an anisotropic nanocrystalline rare earth permanent magnet and a preparation method thereof, which includes the following preparation steps: S1. The component is Nd 29.89 Fe 62.62 Co 5.93 Ga 0.64 B 0.92 (wt.%), the molten alloy ingot is quenched, the linear speed of the quenching roller is 28 m / s, and nanocrystalline quenched magnetic powder with a particle size of 50 to 450 μm is obtained. The nanocrystalline quenched magnetic powder is an isotropic magnetic powder with an equiaxed crystal structure, and the average crystal grain size of the equiaxed crystal is 40 nm. 70 Cu 30The alloy ingot was mechanically crushed to obtain alloy powder with an average particle size of 100 μm. The physical phase of the alloy powder was measured by XRD. As shown in Figure 1, the crushed alloy powder contained Ca phase and Ca2Cu phase, and was not oxidized. 70 Cu 30 The alloy powder and the nanocrystalline quenched magnetic powder are mixed in three dimensions to obtain raw powder. The raw powder is an isotropic raw powder, the mixing time is 2h, and the protective atmosphere is argon gas. In the prepared raw powder, Ca 70 Cu 30 The amounts of alloy powder added were 0.5 wt.%, 1.0 wt.%, 1.5 wt.%, and 2.0 wt.% of the nanocrystalline quenched magnetic powder, respectively.

[0045] S2. The raw material powder obtained in S1 is subjected to hot working treatment, which specifically includes the following steps: S2.1 Raw powders of different compositions are mixed in a vacuum chamber with a degree of vacuum of 1×10 -2 The powder was prepared under the conditions of 650℃, 200MPa, and 99% density. S2.2 The base material is subjected to hot deformation treatment to obtain anisotropic nanocrystalline magnets. The hot deformation temperature is 780℃ and the vacuum degree is 1×10 -2 Pa, the hot deformation rate is 0.1 mm / s, and the deformation amount in the height direction of the base material is 70%.

[0046] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the nanocrystalline quenched magnetic powder of Comparative Example 1 contains Ca. 70 Cu 30 The manufacturing steps are the same as those in Example 1 except for the addition of alloy powder.

[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the nanocrystalline quenched magnetic powder of Comparative Example 2 contains Al. 70 Cu 30 Add alloy powder to Al 70 Cu 30 The amount of alloy powder added is 1 wt % of the mass of the nanocrystalline quenched magnetic powder, and the other manufacturing steps are the same as those in Example 1.

[0048] Table 1 shows the magnetic properties of the different magnets prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0049] Table 1. Magnetic performance of anisotropic nanocrystalline magnets JPEG0007658651000002.jpg51170

[0050] From Table 1, a certain amount of Ca 70 Cu 30 It can be seen that the addition of alloy can greatly improve the coercivity of anisotropic nanocrystalline rare earth permanent magnets, and the addition amount is preferably 0.5-1.5wt.%, more preferably 0.5-1.0wt.%. As can be seen from Fig. 2(a), in the hot deformed magnet without adding Ca-Cu alloy in Comparative Example 1, the white Nd-rich phase is rich at the interface of the magnetic powder and exhibits a strip shape, and the independent dot-like phase in the Nd-rich phase is a rare earth oxide, and as can be seen from Fig. 2(b), there are coarse grains at the interface of the magnetic powder in the magnet, the coarse grains are equiaxed crystals, the average crystal grain size of the equiaxed crystals is 550nm, the volume fraction of the coarse grain region in the Nd-Fe-B matrix phase is 13.5%, and the volume fraction of the coarse grain region is calculated as the volume of the coarse grain region and the volume of the rare earth permanent magnet. The volume fraction of the coarse grain region was determined by first testing a cross section parallel to the c-axis (easy axis of magnetization) of the magnet using a scanning electron microscope (SEM), and then statistically calculating the average value of the ratio between the sum of the areas of the coarse grain regions in five low-magnification SEM images and the total area of ​​the magnet using Image-Pro Plus software. As can be seen from Figure 2(c), the Nd-Fe-B matrix phase is composed of the regularly arranged main phase Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14 The c-axes (thickness direction of crystal grains) of the sheet-like nanocrystals of B are aligned parallel to each other, and the main phase, NdFe 14 The average crystal grain size in the length direction of the sheet-shaped nanocrystals of B is 300 nm, the average crystal grain size in the thickness direction is 100 nm, and the length-to-thickness ratio of the sheet-shaped nanocrystals is 3.

[0051] As can be seen from Fig. 3(a), in the hot-deformed magnet with 0.5wt.% Ca-Cu alloy added, the white Nd-rich phase at the interface of the magnetic powder is reduced; as can be seen from Fig. 3(b), there are coarse grains at some of the magnetic powder interfaces, and the coarse grains are equiaxed crystals. The average crystal grain size of the equiaxed crystals is 512nm, and the volume fraction of the coarse grain region is 8% statistically; the black grain phase of the Ca-Cu alloy is distributed at the interface of the magnetic powder; as can be seen from Fig. 3(c), the Nd-Fe-B matrix phase is the regularly arranged main phase of Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14 The c-axes (thickness direction of crystal grains) of the sheet-like nanocrystals of B are aligned parallel to each other, and the main phase, NdFe 14 The average crystal grain size in the length direction of the sheet-like nanocrystals of B is 290 nm, the average crystal grain size in the thickness direction is 95 nm, and the length-to-thickness ratio of the sheet-like nanocrystals is 3.05.

[0052] As can be seen from Fig. 4(a), in the hot deformed magnet with 1.0wt.% Ca-Cu alloy added, only a small amount of rich white Nd-rich phase exists at the interface of the magnetic powder, the Nd-rich phase at the interface of the magnetic powder is basically completely suppressed, and the black particle phase of the Ca-Cu alloy is distributed at the interface of the magnetic powder; as can be seen from Fig. 4(b), the coarse grains at the interface of the magnetic powder are greatly reduced, and the volume fraction of the coarse grain region is statistically less than 1% and more than 0.5%. From the above, it can be seen that the coarse grains of the hot deformed magnet are basically completely suppressed, and the coarse grain region basically disappears; as can be seen from Fig. 4(c), the Nd-Fe-B matrix phase is the regularly arranged main phase Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14 The c-axes (thickness direction of crystal grains) of the sheet-like nanocrystals of B are aligned parallel to each other, and the main phase, NdFe 14 The average crystal grain size in the length direction of the sheet-like nanocrystals of B is 280 nm, the average crystal grain size in the thickness direction is 80 nm, and the length-to-thickness ratio of the sheet-like nanocrystals is 3.5.

[0053] As can be seen from Fig. 5(a), in the hot deformed magnet with 2.0wt.% Ca-Cu alloy added, the black particle phase is enriched at the interface of the magnetic powder, and there is no enriched white Nd-rich phase at the interface of the magnetic powder; as can be seen from Fig. 5(b), as the Ca-Cu alloy content is further increased, the aggregation phenomenon of Ca-Cu alloy particles appears at the interface of the magnetic powder inside the magnet, which makes the microstructure inside the magnet uneven and reduces the magnetic performance of the magnet; statistically, the volume fraction of the coarse grain region is less than 1%; as can be seen from Fig. 5(c), the Nd-Fe-B matrix phase is the regularly arranged main phase of Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14 The c-axes (thickness direction of crystal grains) of the sheet-like nanocrystals of B are aligned parallel to each other, and the main phase, NdFe 14 The average crystal grain size in the length direction of the sheet-shaped nanocrystals of B is 281 nm, the average crystal grain size in the thickness direction is 79 nm, and the length-to-thickness ratio of the sheet-shaped nanocrystals is 3.56.

[0054] As can be seen from the above analysis, adding an appropriate amount of Ca-Cu alloy to anisotropic nanocrystalline rare earth permanent magnets can, on the one hand, suppress the formation of coarse grains at the magnet interface, and, on the other hand, improve the structure of the main phase RE2Fe 14 It is possible to refine the crystal grains of the sheet-shaped nanocrystals of B, and also to suppress the enrichment of the Nd-rich phase at the interfaces of the magnetic powder, increase the content of the Nd-rich phase between the crystal grains of the main phase inside the magnet, increase the pinning effect of the grain boundary phase on the domain walls, and improve the coercive force of the magnet.

[0055] Furthermore, as can be seen from FIG. 6(a), in the hot-deformed magnet without adding Ca-Cu alloy in Comparative Example 1, there exists a large amount of granular rare earth oxide Nd-O phase in the Nd-rich phase at the interface of the magnetic powder inside the magnet; as can be seen from FIG. 6(b), in the hot-deformed magnet with adding 1.0 wt.% Ca-Cu alloy in Example 1, the rare earth oxide Nd-O phase at the interface of the magnetic powder reacts with some Ca-Cu alloy to form Ca-Cu-O phase, which can be further confirmed from the TEM-EDS spectrogram of the hot-deformed magnet; referring to FIG. 7, the EDS element mapping of the particle phase in the frame selection area in FIG. 7(a) shows that the particle phase in the frame selection area is composed of three elements, namely Ca, Cu, and OCu, as shown in FIG. 7(b)-7(f); the unreacted Ca-Cu alloy is kept as Ca-Cu phase in the hot-deformed magnet, and the Ca-Cu alloy is converted into the main phase NdFe 14 From 7(a), 7(b), and 7(c), 7(b) and the main phase Nd2Fe 14 The sheet-like nanocrystals of B and the Nd-rich phase at the grain boundary can be intuitively seen, and the Nd-rich phase at the grain boundary is continuously distributed at the grain boundary, which improves the pinning effect, and therefore the coercivity of the hot-deformed magnet is greatly improved.

[0056] The hot-deformed magnet of Example 1 was added with 1.0 wt.% Ca. 70 Cu 30 In comparison with the addition of the alloy, the hot-deformed magnet of Comparative Example 2 had 1.0 wt.% Al 70 Cu 30 The remanence of the hot-deformed magnet prepared in Comparative Example 2 by adding alloys was greatly reduced, and the improvement of coercivity was low, mainly because the magnetic powder interface of the hot-deformed magnet still contained a relatively large amount of coarse grains, and the volume fraction of the coarse grain region was statistically 12%. Although the Al and Cu elements could improve the grain boundary components of the nanocrystalline magnet by diffusing, the coarse grain region at the interface of the nanocrystalline magnet could not be effectively suppressed, so the remanence of the magnet was significantly reduced, and the improvement of the coercivity was low.

[0057] Example 2 This embodiment provides an anisotropic nanocrystalline rare earth permanent magnet and its preparation method, the preparation method is as follows: S1. The component is Nd 29.39 Ce 0.5 Fe 62.76 Co 5.93 Ga 0.5 B 0.92 (wt.%), the molten alloy ingot is quenched at a linear speed of 35 m / s to obtain amorphous quenched magnetic powder having a particle size of 50 to 450 μm, and the amorphous quenched magnetic powder is an isotropic magnetic powder. 65 Cu 35 The alloy ingot was mechanically crushed to obtain alloy powder with an average particle size of 100 μm. 65 Cu 35 The alloy powder and the amorphous quenched magnetic powder are mixed in three dimensions to obtain raw powder. The raw powder is an isotropic raw powder, the mixing time is 2 hours, and the protective atmosphere is argon gas. In the prepared raw powder, Ca 65 Cu 35 The amount of the alloy powder added was 1.0 wt. % of the mass of the amorphous quenched magnetic powder.

[0058] S2. The raw material powder obtained in S1 is subjected to hot working treatment, which specifically includes the following steps: S2.1 Raw powder is placed in a vacuum of 1×10 -2 The hot-rolled blank was prepared under the conditions of 680°C, 200MPa, and 99% density. S2.2 The hot-rolled blank is subjected to hot extrusion deformation treatment to obtain an anisotropic nanocrystalline magnetic ring with a wall thickness of 2 mm and an outer diameter of 30 mm. The hot extrusion temperature is 750°C, the hot extrusion speed is 0.1 mm / s, and the vacuum degree is 1×10 -2 It is Pa.

[0059] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that in Comparative Example 3, Ca 65 Cu 35The only difference is that no alloy powder is added, and the other manufacturing steps are the same as those in Example 2. Table 2 shows the magnetic properties of the anisotropic nanocrystalline magnetic rings prepared in Example 2 and Comparative Example 3.

[0060] Table 2. Magnetic performance of anisotropic nanocrystalline magnetic rings JPEG0007658651000003.jpg39170

[0061] As can be seen by comparing the anisotropic nanocrystalline rare earth permanent magnets prepared in Example 2 and Comparative Example 3, in Example 2, 1.0 wt.% Ca 65 Cu 35 After adding the alloy, the coercivity of the hot-extruded magnetic ring was significantly improved. As shown by the measured SEM results, the main phase of the Nd-Fe-B hot-extruded magnetic ring without the alloy was Nd2Fe 14 The average crystal grain size in the length direction of the sheet-like nanocrystals of B is 240 nm, and the average crystal grain size in the thickness direction is 110 nm. A large amount of coarse equiaxed crystals exists at the interface of the magnetic powder inside the magnetic ring. The volume fraction of the coarse grain region is statistically 11.5%. In addition, a large amount of rare earth oxide Nd-O phase exists at the interface of the magnetic powder. 1.0wt.% Ca 65 Cu 35 At the interface of the magnetic powder inside the hot-extruded magnetic ring with added alloy, the rare earth oxide Nd-O phase basically disappears, the enrichment of the Nd-rich phase at the interface of the magnetic powder is suppressed, the Ca-Cu phase and the Ca-Cu-O phase are uniformly distributed at the interface, and the matrix phase is the regularly arranged main phase Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14 The c-axes (thickness direction of crystal grains) of the sheet-shaped nanocrystals of B are aligned parallel to each other, and the main phase of the magnetic ring, NdFe 14 The grain size of the sheet-shaped nanocrystals of B is also refined, and the main phase, Nd2Fe 14The average crystal grain size in the length direction of the sheet-shaped nanocrystals of B was 235 nm, the average crystal grain size in the thickness direction was 105 nm, the length-to-thickness ratio of the sheet-shaped nanocrystals was 2.24, and statistically, it was found that the volume fraction of the coarse grain region was less than 1%, and the coarse grains at the interface were suppressed.

[0062] Example 3 This embodiment provides an anisotropic nanocrystalline rare earth permanent magnet and its preparation method, the preparation method is as follows: S1. The component is Nd 30.2 Fe 62.45 Co 5.93 Ga 0.5 B 0.92 (wt.%), the molten alloy ingot is quenched, the linear speed of the quenching roller is 25 m / s, and nanocrystalline quenched magnetic powder with a particle size of 50 to 450 μm is obtained, and the nanocrystalline quenched magnetic powder is an isotropic magnetic powder. The nanocrystalline quenched magnetic powder is kept at 730°C for 30 minutes in a vacuum, and the degree of vacuum is 5×10 -3 The composition is Ca Pa, and an isotropic nanocrystalline magnetic powder having a sheet-like crystal structure is obtained. The average crystal grain size in the length direction of the sheet-like crystal is 240 nm, and the average crystal grain size in the thickness direction is 95 nm. 70 Cu 30 The alloy ingot was mechanically crushed to obtain alloy powder with an average particle size of 100 μm. 70 Cu 30 The alloy powder and the isotropic nanocrystalline magnetic powder with sheet-like crystal structure were mixed in three dimensions to obtain isotropic raw powder. The mixing time was 2 h, and the protective atmosphere was argon gas. In the prepared raw powder, Ca 70 Cu 30 The amounts of the alloy powder added are 1.5 wt. % and 2.0 wt. % of the isotropic nanocrystalline magnetic powder with sheet-like crystal structure, respectively.

[0063] S2. The raw material powder obtained in S1 is subjected to hot working treatment, which specifically includes the following steps: S2'. Raw powders of different components are placed in a vacuum chamber with a degree of vacuum of 1×10 -2Under the conditions of 680°C and 700°C, the raw powder is directly extruded into an anisotropic nanocrystalline magnetic ring by an extruder, the diameter of the magnetic ring is 20mm, and the wall thickness is 2.5mm. Table 3 shows the magnetic properties of the anisotropic magnetic ring.

[0064] Table 3. Magnetic performance of anisotropic magnetic rings JPEG0007658651000004.jpg24170

[0065] As can be seen from the magnetic properties in Table 3, the low melting point Ca 70 Cu 30 After adding the alloy, the magnetic powder can be directly extruded into anisotropic magnetic ring. As shown by the measured SEM results, the Ca-Cu alloy is distributed at the interface of the magnetic powder, and some of the Ca-Cu alloy reacts with the rare earth oxide to form Ca-Cu-O phase, while the unreacted Ca-Cu alloy is retained as Ca-Cu phase. 1.5wt.%Ca 70 Cu 30 The Nd-Fe-B matrix phase inside the hot-extruded magnetic ring containing the alloy is composed of the regularly arranged main phase Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14 The average crystal grain size in the length direction of the sheet-shaped nanocrystals of B is 280 nm, the average crystal grain size in the thickness direction is 100 nm, the length-to-thickness ratio of the sheet-shaped nanocrystals is 2.8, and the volume fraction of the coarse grain region is statistically less than 1%. 2.0wt.%Ca 70 Cu 30 The main phase Nd2Fe inside the hot-extruded magnetic ring with alloying additions 14 The average crystal grain size in the length direction of the sheet-shaped nanocrystals of B was 279 nm, the average crystal grain size in the thickness direction was 100 nm, the length-to-thickness ratio of the sheet-shaped nanocrystals was 2.79, and statistically, it was found that the volume fraction of the coarse grain region was less than 1%, and coarse grains at the interface were suppressed.

[0066] Example 4 This embodiment provides an anisotropic nanocrystalline rare earth permanent magnet and its preparation method, the preparation method is as follows: S1. The component is Nd 30.2 Fe 62.45 Co 5.93 Ga 0.5 B 0.92 The alloy ingot was quenched at a linear speed of 25 m / s to obtain nanocrystalline quenched magnetic powder with a particle size of 50 to 450 μm. The nanocrystalline quenched magnetic powder was held at 730°C for 30 min in a vacuum with a vacuum degree of 5×10 -3 Pa, and an isotropic nanocrystalline magnetic powder having a sheet-like crystal structure is obtained, and the average crystal grain size in the length direction of the sheet-like crystal is 240 nm, and the average crystal grain size in the thickness direction is 95 nm. Next, the isotropic nanocrystalline magnetic powder having a sheet-like crystal structure is subjected to hot rolling deformation, and the hot rolling temperature is 750°C, and the thickness of the magnetic powder is reduced by 65%, and an anisotropic nanocrystalline magnetic powder having a sheet-like form is obtained, and the length-to-thickness ratio of the sheet-like magnetic powder is 1.5-30, and the easy magnetization direction of the sheet-like magnetic powder is parallel to the thickness direction of the magnetic powder, and the performance of the prepared magnetic powder is: B r =13.6kGs,H ci =14.5kOe, (BH) max =43.8MGOe. The component is Ca 70 Cu 30 The alloy ingot was mechanically crushed to obtain alloy powder with an average particle size of 100 μm. 70 Cu 30 The alloy powder and the prepared anisotropic nanocrystalline magnetic powder in sheet form were subjected to three-dimensional material mixing to obtain anisotropic raw powder. The material mixing time was 2 hours, and the protective atmosphere was argon gas. In the prepared raw powder, Ca 70 Cu 30 The amount of the alloy powder added was 1.0 wt. % of the mass of the anisotropic nanocrystalline magnetic powder.

[0067] S2. The raw material powder obtained in S1 is subjected to hot working treatment, which specifically includes the following steps: S2'. Raw powder is placed in a vacuum of 1×10 -2The hot-roll sintering was carried out under the conditions of 680°C, 200MPa, 100mPa, and sintering for 5min, and the sheet-shaped anisotropic magnetic powder was aligned in parallel by the uniaxial pressure effect, and an anisotropic magnet was obtained.

[0068] Comparative Example 4 The difference between Comparative Example 4 and Example 4 is that in Comparative Example 4, Ca 70 Cu 30 The only difference is that no alloy powder was added, and the other manufacturing steps were the same as in Example 4. Table 4 shows the magnetic properties of the anisotropic magnets of Example 4 and Comparative Example 4.

[0069] Table 4. Magnetic performance of anisotropic magnets JPEG0007658651000005.jpg23170

[0070] As can be seen from Table 4, adding an appropriate amount of Ca-Cu alloy in Example 4 can greatly improve the coercivity of the mechanically aligned anisotropic magnet. As shown by the measured SEM results, there are a large amount of rare earth oxides at the interface of the magnetic powder inside the anisotropic magnet without adding Ca-Cu alloy, the volume fraction of the coarse grain region is 14%, and the main phase Nd2Fe 14 The average crystal grain size in the length direction of the sheet-shaped nanocrystals of NdFeB is 280 nm, the average crystal grain size in the thickness direction is 120 nm, and the length-to-thickness ratio of the sheet-shaped nanocrystals is 2.33. On the other hand, in the anisotropic magnet to which the Ca-Cu alloy is added in Example 4, the Nd-Fe-B matrix phase is the regularly arranged main phase of Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14 The average crystal grain size in the length direction of the sheet-shaped nanocrystals of B is 275 nm, the average crystal grain size in the thickness direction is 115 nm, the length-to-thickness ratio of the sheet-shaped nanocrystals is 2.39, the rare earth oxides at the interface of the magnetic powder basically disappear, the Ca-Cu phase and Ca-Cu-O phase are uniformly distributed at the interface, and the coarse grain regions at the interface of the magnetic powder basically disappear, with the statistical volume fraction of the coarse grain regions being 2%.

[0071] Example 5 This embodiment provides an anisotropic nanocrystalline rare earth permanent magnet and its preparation method, the preparation method is as follows: S1. The component is Nd 30.2 Fe 62.45 Co 5.93 Ga 0.5 B 0.92 The alloy ingot was quenched at a linear speed of 25 m / s to obtain nanocrystalline quenched magnetic powder with a particle size of 50 to 450 μm. The nanocrystalline quenched magnetic powder was held at 730°C for 30 min in a vacuum with a vacuum degree of 5×10 -3 Pa, and an isotropic nanocrystalline magnetic powder having a sheet-like crystal structure is obtained, and the average crystal grain size in the length direction of the sheet-like crystal is 240 nm, and the average crystal grain size in the thickness direction is 95 nm. Next, the isotropic nanocrystalline magnetic powder having a sheet-like crystal structure is subjected to hot rolling deformation, and the hot rolling temperature is 750°C, and the thickness of the magnetic powder is reduced by 65%, and an anisotropic nanocrystalline magnetic powder having a sheet-like form is obtained, and the length-to-thickness ratio of the sheet-like magnetic powder is 1.5-30, and the easy magnetization direction of the sheet-like magnetic powder is parallel to the thickness direction of the magnetic powder, and the performance of the prepared magnetic powder is: B r =13.6kGs,H ci =14.5kOe, (BH) max =43.8MGOe. The component is Mg 85.5 Cu 14.5 The alloy ingot was mechanically crushed to obtain alloy powder with an average particle size of 100 μm. 85.5 Cu 14.5 The alloy powder and the prepared anisotropic nanocrystalline magnetic powder in sheet form were subjected to three-dimensional material mixing to obtain anisotropic raw powder. The material mixing time was 2 hours, and the protective atmosphere was argon gas. In the prepared raw powder, Mg 85.5 Cu 14.5 The amounts of alloy powder added were 0.5 wt %, 1.0 wt %, and 2.0 wt % of the sheet-shaped anisotropic nanocrystalline magnetic powder, respectively.

[0072] S2. The raw material powder obtained in S1 is subjected to hot working treatment, which specifically includes the following steps: S2.1 The raw powder is subjected to orientation molding under a magnetic field of 2T, and the molding pressure is 50MPa. A green compact is obtained by preparing the raw powder. S2.2' Vacuum level 1×10 for the green compact -2 The anisotropic nanocrystalline permanent magnets were prepared by vacuum sintering at 680°C for 20 min under the conditions of 1 Pa and 200°C.

[0073] Comparative Example 5 The difference between Comparative Example 5 and Example 5 is that in Comparative Example 5, Mg 85.5 Cu 14.5 The only difference was that no alloy powder was added, and the other manufacturing steps were the same as in Example 5. Table 5 shows the magnetic properties of the anisotropic magnets prepared in Example 5 and Comparative Example 5.

[0074] Table 5. Magnetic performance of anisotropic magnets JPEG0007658651000006.jpg39170

[0075] As can be seen from Table 5, a certain amount of Mg 85.5 Cu 14.5 Adding an alloy can greatly improve the coercive force of anisotropic nanocrystalline magnets, and an addition amount of 0.5 to 1.0 wt.% is preferable. As shown by the SEM measurement results, in the nanocrystalline sintered magnet of Comparative Example 5, to which no Mg-Cu alloy was added, the main phase Nd2Fe 14 The average crystal grain size in the length direction of the sheet-like nanocrystals of B is 280 nm, and the average crystal grain size in the thickness direction is 105 nm. Coarse grains are present at the interface between the magnetic powders, and the volume fraction of the coarse grain region is statistically found to be 14.5%. A large amount of rare earth oxide phase is also present at the interface between the magnetic powders. In the nanocrystalline sintered magnet with 0.5 wt.% Mg-Cu alloy added in Example 5, the Nd-Fe-B matrix phase is a regularly arranged main phase of Nd2Fe 14 The NdFe2O3 sheet-like nanocrystals and the Nd-rich phase around the grains of the main phase are included. 14The c-axes (thickness direction of crystal grains) of the sheet-like nanocrystals of B are aligned parallel to each other, and the main phase, NdFe 14 The average grain size in the length direction of the sheet-shaped nanocrystals of B is 278 nm, the average grain size in the thickness direction is 102 nm, the length-to-thickness ratio of the sheet-shaped nanocrystals is 2.73, coarse grains exist at some of the magnetic powder interfaces, and the volume fraction of the coarse grain region is statistically 10%. Furthermore, the content of Mg-Cu alloy is increased to 1.0 wt.%, and the main phase Nd2Fe 14 The average grain size in the length direction of the sheet-like nanocrystals of B is 275 nm, the average grain size in the thickness direction is 101 nm, the length-to-thickness ratio of the sheet-like nanocrystals is 2.72, and the volume fraction of the coarse grain region is 2.5%. When the content of the Mg-Cu alloy is 2.0 wt.%, the main phase Nd2Fe 14 The average grain size of the sheet-shaped nanocrystals of B in the length direction is 275nm, the average grain size in the thickness direction is 100nm, the ratio of the length to the thickness of the sheet-shaped nanocrystals is 2.75, and the volume fraction of the coarse grain region is 2.5%. Therefore, the appropriate amount of Mg-Cu alloy can suppress the formation of coarse grains at the interface, and after the amount of Mg-Cu alloy powder added reaches 1.0wt.%, on the one hand, the rare earth oxides at the interface of the sintered magnet basically disappear, and the Mg-Cu phase and Mg-Cu-O phase are uniformly distributed at the interface; on the other hand, it can suppress the enrichment of the Nd-rich phase at the interface of the magnetic powder, improve the content of the Nd-rich phase between the crystal grains of the main phase inside the magnetic powder, increase the pinning effect of the grain boundary to the domain wall, and improve the coercive force of the magnet.

[0076] It should be understood that the application of the present invention is not limited to the above examples, and those skilled in the art can improve or convert it according to the above description, and all these improvements and conversions all fall within the scope of protection of the appended claims of the present invention.

Claims

1. An anisotropic nanocrystalline rare earth permanent magnet, the rare earth permanent magnet comprising a RE-Fe-B matrix phase and a second phase; The RE-Fe-B matrix phase is a regularly arranged main phase of RE 2 Fe 14 The RE-rich phase is located around the sheet-like nanocrystals of B and the crystal grains of the main phase, and the main phase is RE 2 Fe 14 B, the sheet-shaped nanocrystal has an average crystal grain size in the length direction of 70-800 nm, an average crystal grain size in the thickness direction of 30-200 nm, and the length-to-thickness ratio of the sheet-shaped nanocrystal is greater than 1.2; The volume fraction of the coarse grain region in the RE-Fe-B matrix phase is 10% or less, and is calculated as the volume of the coarse grain region and the volume of the rare earth permanent magnet, and the coarse grain region refers to an equiaxed crystal region having a crystal grain size of more than 500 nm; The second phase comprises at least one of an M-Cu phase and an M-Cu-O phase, where M is at least one of Ca and Mg.

2. The rare earth permanent magnet is prepared from a raw material powder obtained by mixing RE-Fe-B magnetic powder and M-Cu alloy powder, where M is at least one of Ca and Mg, and the components of the RE-Fe-B magnetic powder are RE x Fe 100-x-y-z T.M. y B z and RE is one or more of La, Ce, Pr, Nd, Y, Dy, Tb, and Ho; TM is one or more of Co, Zr, Cr, V, Nb, Si, Ti, Mo, Mn, W, Ga, Cu, Al, and Zn; 2. The anisotropic nanocrystalline rare earth permanent magnet of claim 1, wherein x, y, and z are mass fractions of the elements, where 26.0≦x≦36.0, 0.14≦y≦8.0, and 0.8≦z≦1.

36.

3. 3. The anisotropic nanocrystalline rare earth permanent magnet according to claim 2, wherein, calculated as the mass of the RE-Fe-B magnetic powder, the amount of the M-Cu alloy powder is 0.1-5.0 wt.%, the mass percentage of Cu in the Ca-Cu alloy powder is 10-60 wt.%, the mass percentage of Cu in the Mg-Cu alloy powder is 1-50 wt.%, and the mass percentage of Cu in the Ca-Mg-Cu alloy powder is 10-50 wt.%.

4. The anisotropic nanocrystalline rare earth permanent magnet according to any one of claims 1 to 3, characterized in that the volume fraction of the coarse grain region in the RE-Fe-B matrix phase is 1% or less, and is calculated as the volume of the coarse grain region and the volume of the rare earth permanent magnet.

5. A method for preparing anisotropic nanocrystalline rare earth permanent magnets according to any one of claims 1 to 3, comprising the steps of: A preparation step S1 of obtaining a raw material powder which is at least one of anisotropic raw material powder and isotropic raw material powder by mixing an RE-Fe-B magnetic powder containing at least one of anisotropic magnetic powder and isotropic magnetic powder with an M-Cu alloy powder in which M is at least one of Ca and Mg; The main phase is RE 2 Fe 14 and a preparation step S2 of subjecting the raw material powder prepared in step S1 to hot working treatment so as to arrange the sheet-shaped nanocrystals of B in a regular arrangement, thereby obtaining the anisotropic nanocrystalline rare earth permanent magnet.

6. A method for preparing an anisotropic nanocrystalline rare earth permanent magnet as described in claim 5, characterized in that the hot processing process in step S2 includes at least one of hot deformation processing, hot extrusion deformation processing, magnetic field oriented sintering molding processing, and mechanically oriented sintering molding processing.

7. The hot deformation treatment is Step S2.1: preparing the raw material powder into a body having a density of 50% to 99.99% at a temperature of room temperature to 800° C.; The method for preparing anisotropic nanocrystalline rare earth permanent magnets according to claim 6, further comprising a step S2.2 of subjecting the base material to hot deformation treatment at a temperature of 600-850°C, a deformation amount of 30%-90%, and a deformation speed of 0.01-3.5 mm / s so as to arrange the sheet-shaped nanocrystals of RE 2 Fe 14 B, which is the main phase, in a regular arrangement.

8. The hot extrusion deformation treatment is Step S2.1: preparing the raw material powder into a body having a density of 50% to 99.99% at a temperature of room temperature to 800° C.; The method for preparing an anisotropic nanocrystalline rare earth permanent magnet according to claim 6, further comprising: step S2.2 of subjecting the base material to hot extrusion deformation at a temperature of 600 to 850°C so as to arrange the sheet-shaped nanocrystals of the main phase RE 2 Fe 14 B in a regular arrangement; or step S2' of subjecting the raw material powder to hot extrusion deformation at a temperature of 600 to 850°C so as to arrange the sheet-shaped nanocrystals of the main phase RE 2 Fe 14 B in a regular arrangement.

9. The magnetic field orientation sintering molding process is Step S2.1: subjecting the anisotropic raw material powder to an orientation molding process under an external magnetic field condition of 1 to 3 T to prepare a green compact; The method for preparing an anisotropic nanocrystalline rare earth permanent magnet according to claim 6, further comprising: step S2.2 of subjecting the green compact to hot-rolling sintering or pressureless sintering at a hot-rolling sintering temperature of 450-850°C, a pressure of 50-500 MPa, and a time of 1-60 min; or step S2.2' of subjecting the green compact to pressureless sintering at a sintering temperature of 600-850°C, and a time of 10-120 min.

10. The mechanically oriented sintering molding process includes: Step S2' of performing hot rolling orientation sintering on the anisotropic raw material powder (the RE-Fe-B magnetic powder of the anisotropic raw material powder is a sheet-shaped magnetic powder having a length-to-thickness ratio of 1.2 to 30, and the easy magnetization direction of the sheet-shaped magnetic powder is parallel to the thickness direction of the sheet-shaped magnetic powder) under a uniaxial pressure of 50 to 500 MPa at a sintering temperature of 450 to 850 ° C. and a sintering time of 1 to 60 min; or Step S2.1 '' of performing cold rolling molding at room temperature on the anisotropic raw material powder (the RE-Fe-B magnetic powder of the anisotropic raw material powder is a sheet-shaped magnetic powder having a length-to-thickness ratio of 1.2 to 30, and the easy magnetization direction of the sheet-shaped magnetic powder is parallel to the thickness direction of the sheet-shaped magnetic powder) under a uniaxial pressure to obtain a green compact having a density of 40% to 70%; and S2.2″, performing pressureless sintering on the green compact at a sintering temperature of 600-850° C. for a sintering time of 10-120 min.

Citation Information

Patent Citations

  • Mg-Cu grain boundary modified high-magnetism sintered Nd-Fe-B magnet and preparation process thereof

    CN103971875A

  • Neodymium-iron-boron magnet and method for regulating and controlling grain size and grain size distribution of coarse grain layer of neodymium-iron-boron magnet

    CN111755237A

  • Nanocrystalline and nanocomposite rare earth permanent magnet materials and method of making the same

    CN1735947A

  • Highly oxidation-resistant alloy powder for rare-earth magnet, its manufacture, and rare-earth sintered magnet using the same

    JP1999251123A

  • Anisotropic Nanocomposite Rare Earth Permanent Magnets and Their Manufacturing Methods

    JP2008505500A